Strawberry notch 1 safeguards neuronal genome via regulation of Yeats4 expression - Dai Ihara; Ayano Narumoto; Yukie Kande; Tomoki Hayashi; Yasuaki Ikuno; Manabu Shirai; Masaki Wakabayashi; Ryo Nitta; Hayato Naka-Kaneda; Yu Katsuyama (Cell Death Discovery)
Abstract Neurons are subjected to various stresses, including high metabolic demand, physiological activity, and transcriptional regulation, to which their genomic DNA are vulnerable. Genome stability of neurons is essential for proper physiological brain function. Failure in accurate genomic DNA repair can result in abnormal neuronal functions or cell death. Genomic instability has been implicated in increased risks of neurodevelopmental and neurodegenerative disorders. However, the molecular mechanisms underlying neuronal genome stability remain poorly understood. Mutations in the Strawberry Notch Homolog 1 (SBNO1) have been suggested to contribute to these disorders. Here, we investigated the molecular mechanisms underlying histological abnormalities observed in the cortex of Sbno1 knockout (KO) mice. Comprehensive gene expression analysis revealed that Sbno1 KO affects the expression of genes related to cell survival, consistent with the increased apoptosis observed in Sbno1 KO cortices. Among the genes downregulated in Sbno1 KO, we focused on Yeats4. Overexpression of Yeats4 rescued the accumulation of genomic DNA damage and cell death caused by Sbno1 deletion. These findings suggest that Sbno1 is critical in safeguarding the neuronal genome, at least in part, via regulating Yeats4 expression.